The effect of tidal currents on the hydrodynamics of tidal turbine systems - Firmadany Bayu; Ikhwan Muhammad; Saputra T. Murdani; Muttaqin Mohd Iqbal; Kazrina Cut Shilvani Maghfirahtil (BIO Web of Conferences)
The ocean is a highly potential source of renewable energy with various forms, including wave and tidal energy. Due to its vast composition, the ocean stores and transfers significant amounts of energy. This study focuses on analyzing tidal dynamics that affect the stability of tidal turbines. The method used involves developing a model between the hydrodynamics of the turbine blades and the protection of the generator, assuming that the blades have an optimal angle to harness various tidal current speeds. The generator is then examined through d-q diagram performance. The results indicate that the model’s stability depends on the initial d-q current strength without external current influence. Disturbances in the hydrodynamics of the turbine blades were found to affect the generator’s stability. The generator's voltage limit and the tolerance limit for tidal current strength have been determined to be at stationary conditions.